Physical activity and physical fitness in children with heritable connective tissue disorders - de Koning, Lisanne; Warnink-Kavelaars, Jessica; van Rossum, Marion; Limmen, Selina; Van der Looven, Ruth; Muiño-Mosquera, Laura; van der Hulst, Annelies; Oosterlaan, Jaap; Rombaut, Lies; Engelbert, Raoul; , on behalf of the Pediatric Heritable Connective Tissue Disorders Study Group (Frontiers in Pediatrics, 2023)
Objectives: Health problems in patients with heritable connective tissue disorders (HCTD) are diverse and complex and might lead to lower physical activity (PA) and physical fitness (PF). This study aimed to investigate the PA and PF of children with heritable connective tissue disorders (HCTD). Methods: PA was assessed using an accelerometer-based activity monitor (ActivPAL) and the mobility subscale of the Pediatric Evaluation of Disability Inventory Computer Adaptive Test (PEDI-CAT). PF was measured in terms of cardiovascular endurance using the Fitkids Treadmill Test (FTT); maximal hand grip strength, using hand grip dynamometry (HGD) as an indicator of muscle strength; and motor proficiency, using the Bruininks-Oseretsky Test of Motor Proficiency-2 (BOTMP-2). Results: A total of 56 children, with a median age of 11.6 (interquartile range [IQR], 8.8-15.8) years, diagnosed with Marfan syndrome (MFS), n=37, Loeys-Dietz syndrome (LDS), n=6, and genetically confirmed Ehlers-Danlos (EDS) syndromes, n =13 (including classical EDS n=10, vascular EDS n=1, dermatosparaxis EDS n=1, arthrochalasia EDS n=1), participated. Regarding PA, children with HCTD were active for 4.5 (IQR 3.5-5.2) hours/day, spent 9.2 (IQR 7.6-10.4) hours/day sedentary, slept 11.2 (IQR 9.5-11.5) hours/day, and performed 8,351.7 (IQR 6,456.9-1,0484.6) steps/day. They scored below average (mean (standard deviation [SD]) z-score -1.4 (1.6)) on the PEDI-CAT mobility subscale. Regarding PF, children with HCTD scored well below average on the FFT (mean (SD) z-score -3.3(3.2)) and below average on the HGD (mean (SD) z-score -1.1 (1.2)) compared to normative data. Contradictory, the BOTMP-2 score was classified as average (mean (SD) z-score .02 (.98)). Moderate positive correlations were found between PA and PF (r(39)=.378, p<.001). Moderately sized negative correlations were found between pain intensity and fatigue and time spent actively (r(35)=.408, p<.001 and r(24)= .395 p<.001, respectively). Conclusion: This study is the first to demonstrate reduced PA and PF in children with HCTD. PF was moderately positively correlated with PA and negatively correlated with pain intensity and fatigue. Reduced cardiovascular endurance, muscle strength, and deconditioning, combined with disorder-specific cardiovascular and musculoskeletal features, are hypothesized to be causal. Identifying the limitations in PA and PF provides a starting point for tailor-made interventions.